ANALISIS KEPUASAN MAHASISWA UNIVERSITAS UDAYANA TERHADAP SISTEM LAYANAN INFORMASI IMISSU - YUDIANDARI, NI MADE SHINTYA; GANDHIADI, G. K.; SUSILAWATI, MADE (E-Jurnal Matematika, 2024)
Information is a valuable asset in digital era. Government , educational institutions, and public service organizations face increasing expectations to manage information properly and efficiently. This problem can be solve by information system service. The success of an information service system can be measured by user satisfaction. Udayana University has several information service systems. One of the information service systems owned by Udayana University is IMISSU (Integrated Management Information System the Strategic of Udayana). Our research aims to study the analysis student satisfaction at Udayana University. We used partial least square modeling with five construct namely quality of information, quality of system, quality of service, perceived usefulness, and student satisfaction. The results of this research are all construct of this model  has significant influence on student satisfaction quality of system has significant influence on student satisfaction with mediation of perceived usefulness and quality of system is the most variable influence on college student satisfaction.